Spontaneous extradural hematoma as a presentation of sinusitis: Case report and literature review - Saisawat Chaiyasate (2018)
Spontaneous extradural hematoma is rarely mentioned in literature as intracranial complications of sinusitis. The authors presented a girl with spontaneous extradural hematoma secondary to pansinusitis and reviewed the literature. In a child with spontaneous extradural hematoma without a history of head trauma, sinusitis should be excluded. © 2007 Elsevier Ireland Ltd. All rights reserved.